1994
DOI: 10.1080/15257779408012158
|View full text |Cite
|
Sign up to set email alerts
|

DNA Diagnosis of Ovale Malaria and Malariae Malaria Using Microtiter Plate-Hybridization

Abstract: We have developed a colorimetric assay, "microtiter plate-hybridization", for the detection of human malaria parasite, Plasmodium ovule and Plasmodium malariae, in which the target DNA sequence of the 18s ribosomal RNA gene is amplified by polymerase chain reaction and hybridized with the species-specific probes immobilized on a microtiter well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…As an alternative measure, the PCRbased MPH assay was tested for its practical utility and reported as a useful tool for the differential diagnosis of various species of malaria. [11][12][13] In the present study, we confirmed the usefulness and feasibility of the PCR-based MPH technique for the genetic diagnosis of the reemerging Korean P. vivax malaria. Using this technique it was possible to provide a specific diagnosis of human malaria.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…As an alternative measure, the PCRbased MPH assay was tested for its practical utility and reported as a useful tool for the differential diagnosis of various species of malaria. [11][12][13] In the present study, we confirmed the usefulness and feasibility of the PCR-based MPH technique for the genetic diagnosis of the reemerging Korean P. vivax malaria. Using this technique it was possible to provide a specific diagnosis of human malaria.…”
Section: Discussionsupporting
confidence: 63%
“…It is well known that the plasmodial genes encoding 18S rRNA contain species-specific regions: P. vivax, 14 P. falciparum, 15 Plasmodium malariae, 16 Plasmodium ovale, 12 and Plasmodium ovalevariant (showing variations at the probe region, reported from Vietnam). 17 The oligonucleotide primer set (primer MPH-1; 5Ј-CAGATACCGTCGTAATCTTA-3Ј, and primer MPH-2; 5Ј-CCAAAGACTTTGATTT CTCAT-3Ј) cross-reactive for P. vivax, P. falciparum, and P. malariae was used as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations